Coffee with High but Not Low Caffeine Content Augments Fluid and Electrolyte Excretion at Rest - Seal, Adam D.; Bardis, Costas N.; Gavrieli, Anna; Grigorakis, Petros; Adams, J. D.; Arnaoutis, Giannis; Yannakoulia, Mary; Kavouras, Stavros A. (Frontiers in Nutrition, 2017)
Background: Low levels of caffeine ingestion do not induce dehydration at rest, while it is not clear if larger doses do have an acute diuretic effect. The aim of the present investigation was to examine the acute effect of low and high levels of caffeine, via coffee, on fluid balance in habitual coffee drinkers (at least one per day) at rest. Methods: Ten healthy adults (8 males and 2 females; age: 27±5 y, weight: 89.5±14.8 kg, height: 1.75±0.08 m, and body mass index: 29.1±4.4 kg∙m-2) ingested 200 mL of water (W), coffee with low caffeine (3 mg∙kg-1, LCAF), or coffee with high caffeine (6 mg∙kg-1, HCAF) on three respective separate occasions. All sessions were performed at 09:00 in the morning in a counterbalanced, crossover manner, at least 5 days apart. Subjects remained in the laboratory while urine samples were collected every 60 min for three hours post-ingestion. Results: Absolute caffeine consumption was 269±45 and 537±89 mg for the LCAF and HCAF, respectively. Coffee ingestion at the HCAF trial induced greater diuresis during the 3-h period (613±101 mL, P < 0.05), when compared to W (356±53 mL) and LCAF (316±38 mL). Additionally, cumulative urinary osmotic excretion was significantly greater in the HCAF (42592 mmol, P < 0.05), as compared to the W (24936 mmol) and LCAF (17716 mmol) trials. Conclusion: The data indicate that caffeine intake of 6 mg∙kg-1 in the form of coffee can induce an acute diuretic effect, while 3 mg∙kg-1 do not disturb fluid balance in healthy casual coffee drinking adults at rest.